Surgical Planning in Penetrating Abdominal Crohn's Disease - Myrelid, Pär; Soop, Mattias; George, Bruce D. (Frontiers in Surgery, 2022)
Crohn’s disease is increasing globally, and the disease location and behaviour is changing towards more colonic as well as inflammatory behaviour. Surgery was previously mainly performed due to ileal/ileocaecal location and stricturing behaviour, and therefore many anticipate the surgical load to decrease. There are however also data showing an increasing complexity among patients at the time of surgery, with an increasing number of patients with abdominal penetrating disease, requiring a more complex surgery and experiencing more complicated post-operative outcomes. The other major cause of abdominal penetrating Crohn’s disease is secondary to surgical complications, e.g. anastomotic dehiscence or inadvertent enterotomies. To improve the care for patients with penetrating abdominal Crohn’s disease in general, and in the peri-operative phase in particular, the use of multidisciplinary team discussions is essential. In this paper we will give an overview of penetrating abdominal Crohn’s disease today, and how this situation may be handled. Proper surgical planning will decrease the risk of surgically induced penetrating disease and improve the outcome when penetrating disease is already established. It is important to evaluate patients prior to surgery and optimise them with enteral nutrition (or parenteral if enteral nutrition is ineffective) and treat abdominal sepsis with drainage and antibiotics.